2016
DOI: 10.1530/joe-15-0542
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical distribution of δ and PP cells in human pancreatic islets

Abstract: The aim of this study was to evaluate the location of PP and δ cells in relation to the vascularization within human pancreatic islets. To this end, pancreas sections were analysed by immunofluorescence using antibodies against endocrine islet and endothelial cells. Staining in different islet areas corresponding to islet cells adjacent or not to peripheral or central vascular channels was quantified by computerized morphometry. As results, α, PP and δ cells were preferentially found adjacent to vessels. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…A higher percentage of glucagon-producing cells within the islet improves the glucose responsiveness 23,24 . By contrast, somatostatin exerts inhibitory effects on insulin and glucagon secretion 25,26 . A uniform distribution of α-, β- and δ-cells therefore reduces islet heterogeneity and variations for in vitro testing of islet function.…”
Section: Introductionmentioning
confidence: 99%
“…A higher percentage of glucagon-producing cells within the islet improves the glucose responsiveness 23,24 . By contrast, somatostatin exerts inhibitory effects on insulin and glucagon secretion 25,26 . A uniform distribution of α-, β- and δ-cells therefore reduces islet heterogeneity and variations for in vitro testing of islet function.…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that in larger human islets, sub-islet anatomical clusters exist, comprising a core of beta-cells surrounded by alpha-and delta-cells [9]. The alpha-cells were found to be equally distributed between the islet periphery and adjacent to the islet core capillaries, but PP-cell presence was higher in the islet mantle while delta-cells were more abundant in the core [10]. No differences were found between the head and tail of the human pancreas with respect to delta-cell presence, although PP cells are more abundant in the tail.…”
Section: Anatomical Architecture and Vasculature Of Islets Of Langerhansmentioning
confidence: 99%
“…Moreover, it is believed that, in mosaic Comparative Endocrinology of Animals 4 islets, the cells are located without clear ordering. In some studies [25,33,34], it was indicated that mixed (mosaic) islets of Langerhans have a clear, ordered structure. Within these islets, segments restricted by blood vessels have been identified.…”
Section: Pancreas Structure In Adultsmentioning
confidence: 99%